The effect of treatment upon temporal dispersion in IvIg responsive multifocal motor neuropathy. Issue 9 (16th August 2005) - Ghosh, A; Virgincar, A; Kennett, R; Busby, M; Donaghy, M
Abstract : Background: Multifocal motor neuropathy with conduction block (MMN) is a treatable disorder that can be mistaken for other lower motor neurone syndromes. Existing electrophysiological diagnostic criteria for MMN are restrictive. In particular, many are cautious about diagnosing conduction block (CB) in the presence of abnormal temporal dispersion (TD). Objective: To study the significance of TD in MMN, its relationship to CB in intravenous immunoglobulin (IvIg) responsive patients, and its utility in detecting a treatment response. Methods: We compared pre- and post-treatment changes in CB and TD in nine patients who satisfied clinical and electrophysiological criteria for MMN and responded to IvIg. Results: TD improved in one or more nerve segments in eight of nine patients tested. There was marked improvement in 65% of all nerve segments, and 60% of those segments with CB. By comparison, significant improvement in CB occurred in only 33% of segments. Of segments with significantly better CB after treatment, all but one showed similar improvements in TD. Such changes were not related to the degree of TD before treatment, being seen in segments with abnormal as well as normal TD. There was no correlation between improvements seen in TD and CB. Conclusion: We believe that TD should be considered an inherent feature of MMN. Improvement in TD is an independent marker of electrophysiological improvement in this disorder and is likely to be more useful than CB. When MMN is clinically suspected, the use of stringent criteria for CB in the presence of TD should be avoided.